E-Learning Success Model: An Extention of DeLone & McLean IS' Success Model - Henki Bayu Seta; Theresia Wati; Anita Muliawati; Achmad Nizar Hidayanto (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2018)
Learning by using e-learning system at this time become an important part of university to carrying out the education. Learning by e-learning system is very supportive to conventional learning, so it is necessary to measure the success of e-learning implementation. In this article, the research model was developed by integrating. DeLone& McLean IS concept of success model and adoption model of e-learning success. The variables that used in this research is technical system quality, service quality, content and information quality, use, user perceived satisfaction, and individual impact. Data collection is by conducting surveys to e-learning users which is lecturers and students. To test the model that has been developed, conducted a survey on UPN "Veteran" Jakarta with the total number of respondents as many as 180 respondents and obtained 157 respondents who fill the questionnaire correctly. This research, shows both the use and satisfaction of e-learning system have an impact for individual performance. This research also found that educational system quality and technical quality are the main factors that encourage user satisfaction with e-learning system, while the use of e-learning system that influenced by content & information quality, also user perceived satisfaction for e-learning system.